2012
DOI: 10.1590/s1413-70542012000100003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic progress of phenotypic recurrent selection in popcorn

Abstract: Popcorn is widely consumed in the south of Minas Gerais; however, up to now no specific breeding program for the region has been carried out. Recurrent selection (RS) is a viable alternative for breeding of this crop; nevertheless, it is necessary to frequently evaluate the progress achieved. Consequently, the purpose of this work was to assess the genetic progress obtained after two cycles of RS for the traits of popping expansion (PE) and grain yield (GY). Cycles one and two of the UFLA -E and UFLA -R popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Overall, it may be observed that the present results are consistent with those reported by Hallauer et al (2010), who noted that for some traits in corn, performance of three recurrent selection cycles is not sufficient to obtain expressive gains. In the present study, differences among the selection cycles for EV were significantly expressed from the second cycle, which corroborates the findings of Hallauer et al (2010) and Ematné et al (2012), who detected small but significant differences from the second selection cycle.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, it may be observed that the present results are consistent with those reported by Hallauer et al (2010), who noted that for some traits in corn, performance of three recurrent selection cycles is not sufficient to obtain expressive gains. In the present study, differences among the selection cycles for EV were significantly expressed from the second cycle, which corroborates the findings of Hallauer et al (2010) and Ematné et al (2012), who detected small but significant differences from the second selection cycle.…”
Section: Resultssupporting
confidence: 93%
“…The populations UFLA-E 1, UFLA-E 2, UFLA-R 1, and UFLA-R 2 were obtained as described by Ematné et al (2012), and the populations UFLA-E 0 and UFLA-R 0 were derived from the first selection for grain type (rounded or pointed) of the original UFLA population (Ematné et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…However, the growing demand is not being met because of the frequent unavailability of the cultivars registered with the Brazilian Ministry of Agricultural, Livestock, and Food Supply (Ministério da Agricultura, Pecuária e Abastecimento Agrário). Especially, the inability of the public research institutions working on this plant to supply the required number of cultivars is a big obstacle for the expansion of popcorn cultivation (Seifert et al, 2006;Ematné et al, 2012). In this regard, the development of hybrid cultivars deserves special attention from popcorn breeders.…”
Section: Introductionmentioning
confidence: 99%
“…The methodology of recurrent selection is the main alternative, consisting of a cyclical process that increases the frequency of favourable alleles, raising the mean of the main traits without exhausting the genetic variability of the population (HALLAUER; MIRANDA FILHO; CARENA, 2010), although it is believed that the gains are no longer significantly increased in the more advanced cycles. The methodology of recurrent selection has already been used in some studies on popcorn (EMATNÉ et al, 2012;FARIA et al, 2008;GUIMARÃES et al, 2018a;LIMA et al, 2018;REIS et al, 2009;VILARINHO et al, 2002).…”
Section: Introductionmentioning
confidence: 99%